2017
DOI: 10.1136/bmjopen-2016-014981
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting in abstracts of RCTs published in emergency medicine journals: a protocol for a systematic survey of the literature

Abstract: IntroductionThe quality of reporting of abstracts of randomised controlled trials (RCTs) in major general medical journals and in some category-specific journals was shown to be poor before the publication of the ConsolidatedStandards of ReportingTrials (CONSORT) extension for abstracts in 2008, and an improvement in the quality of reporting of abstracts was observed after its publication. The effect of the publication of the CONSORT extension for abstracts on the quality of reporting of RCTs in emergency medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In our study, those MAs published in cancer-speci ed journals showed poorer reporting quality than those published in other journals, while Moher et al have reported a contrast nding [15] . The inconsistent reporting across study may be attributed to the editorial attitude to the reporting guideline [16] . For example, the surgery journals always instructed authors to refer reporting guideline when submitting a MAs [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, those MAs published in cancer-speci ed journals showed poorer reporting quality than those published in other journals, while Moher et al have reported a contrast nding [15] . The inconsistent reporting across study may be attributed to the editorial attitude to the reporting guideline [16] . For example, the surgery journals always instructed authors to refer reporting guideline when submitting a MAs [17] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, users may restrict their query to retrieving only those publications classified as ‘case report’ by constraining the ‘Mesh Terms’-> ‘Identifier’ attribute for the MeSH Terms identifier ‘D002363’ (case reports). Researchers typically rely on abstracts to assess an article for further reading and often; abstracts are the only source of information that are freely available (Germini et al, 2017). To allow the users to easily access and scan article abstracts of interest, we leveraged the attribute ‘Abstract Text’ within the ‘Publication’ class.…”
Section: Additional Data Sources and Data Models In Targetmine Providmentioning
confidence: 99%